(untitled) (The Himalayan Geographers, 2025)
Coffea arabica farming in Kaski, Nepal has become one of the preferred ways of earning a living, yet its long-term sustainability is at risk due to market challenges, pest and diseases. This study attempt to assess the current situation of production and farmers experience, emphasizing the varietal of coffee, issues, and production trends in Kaski district. The research utilized quantitative as well as qualitative data methods including the secondary data on green beans production from 2014 to 2024, further forecasts using Microsoft Excel, and qualitative data were gathered in the form of Focus Group Discussions (FGDs) in three coffee farm location namely Adhikaridanda, Begnas, and Nirmalpokhari with the local coffee growers. The findings indicate a fluctuating and a decline trend in coffee production with predictions showing that the trend may continue to decrease. In addition, farmers preferred Caturra (Yellow and Red), Catimor, Bourbon, Tekisic, Pacas, Selection-10, and Typica varietal to plant in the field. The key constraints were identified through farmers that included pest and diseases outbreaks (notably stem borer and leaf rust), selection of strong diseases resistance strain was not appropriate and lack of knowledge and technical back-up. The commonly used measures was traditional eco-friendly pesticide called Bordeaux mixture (Nilotootho and Chuna), and animal urine are the popular methods to control diseases. In spite of challenges, the farmers expressed optimism about the coffee farming, depending on increasing support of co-operatives, I/NGOs, and government agencies. The study concludes, Coffea arabica farming has significant potential in Kaski, but it requires an initiation to coordinate with research, improving the market access, and access to resistant varietal of coffee seedling.